EARLY GROWTH OF JABON (Anthocephalus cadamba Miq) IN A DRAINED PEATLAND OF PELALAWAN, RIAU - Ahmad Junaedi; Nina Mindawati; Yanto Rochmayanto (Indonesian Journal of Forestry Research, 2021)
The desirability to explore other tree species that can be used to substitute Acacia crassicarpa in forest plantation has increased. One of the early insights that must be known is the growth performances of tree species candidates, especially in planting conditions (site and silviculture) similar to A. crassicarpa plantation. This study evaluated the growth performance of jabon (A. cadamba Miq.) and its relationship with soil properties in a drained peatland. The research was conducted by establishing experimental plots of jabon in a drained peatland (DP) using a randomised complete block design with three spacing (2 m x 3 m, 2.5 m x 3 m, 3 m x 3 m) as treatment and three blocks as replications. The study observed survival, growth and soil chemical properties. At 24 months after planting (MaP), since the toxicity of soil micronutrients was excessive as one of the main factors; the mortality rate of jabon was high (62%), while its growth was poor (height = 259 cm and DBH = 3.74 cm) in drained peatland. However, the study observed that 7% of jabon had good growth, with a range of height growth at 24 MaP of 401–660 cm. These results indicated that though overall jabon did not show good growth in DP, however, it was found that 7% of jabon had promising growth; therefore, it was suggested that through tree improvement program and certain treatments to overcome micronutrient toxicity and weed suppression, the possibility of jabon was able to be developed in a DP for forest plantation is still.